Weed control and crop safety with premixed tolpyralate and bromoxynil on cereals - Seshadri S. Reddy; Ignacio Gonzalez; Rory Degenhardt; David Ouse; Norbert Satchivi; Laura Creemer (Weed Technology)
Corteva Agriscience recently registered a premix of tolpyralate and bromoxynil in the United States and Canada for weed control in cereal fields. Limited information exists on weed control efficacy and crop safety with this new herbicide premixture. Greenhouse trials were conducted for 2 yr to test the efficacy of tolpyralate and bromoxynil combinations on 14 broadleaf and four grass weeds and its safety to wheat and barley. Four combinations of tolpyralate and bromoxynil at a 1:10 ratio (3.75 + 37.5, 7.5+ 75, 11.25 + 112.5, and 15 + 150 g ai ha−1) as a tank mix and premix were tested. Stand-alone treatments of tolpyralate and bromoxynil were also included in this study. The lowest tested rate of tolpyralate (3.75 g ha−1) provided 10% to 98% control of broadleaf weeds and 27% to 77% control of grass weeds. Bromoxynil at the lowest tested rate (37.5 g ha−1) provided 16% to 80% control of broadleaf weeds and 0% to 30% control of grass weeds. Tank mixing these two herbicides at the same rates resulted in improved broadleaf (60% to 100%) and grass (45% to 94%) weed control. The minimum recommended field use rate of tolpyralate + bromoxynil (15 + 150 g ha−1) controlled all the broadleaf weeds by >95%. That combination also controlled green foxtail, barnyardgrass, and large crabgrass by >90%. An additive or synergistic effect between the two herbicides was observed against several broadleaf and grass weed species. Among all the tested weeds, a greater synergistic effect was observed when the herbicides were used on kochia, chickweed, wild mustard, corn poppy, barnyardgrass, green foxtail, and fall panicum. The premix of the two herbicides provided similar control of broadleaf weeds, but better control of grass weeds than the tank-mix combinations. The premix can be used safely on wheat and barley.